Preparedness for Business Programs in Higher Education Among ABM Students: Basis for Intervention Programs - Marianne Farrah T. Segui (Future Science / FSH-PH Publications, 2026)
This study determined the extent of the business programAccountancy, Business, and Management (ABM) respondents from five public senior high schools in Quezon City, District I, were proportionally chosen through a convenient sampling technique from the total population of 471 enrollees in ABM. Using an expert-validated researcher-made questionnaire, the respondents self-assessed their level of competence in 21st-century skills, financial literacy, entrepreneurial skills, and emotional intelligence. The students believed they were well-prepared in communication, personal responsibility, and ICT proficiency but were less prepared in applied financial skills, especially investment management and bookkeeping, and applied entrepreneurial skills, especially prototyping and business modeling. The students also perceived themselves to have moderate-high emotional intelligence, with the lowest degree in emotional regulation. Inferential statistics using the Mann-Whitney U and Kruskal-Wallis H tests yielded only two significant differences: females are more proficient in ICT than males (U = 4381.5, p = .021), and information proficiency is significantly higher in the highest income bracket than in the lowest income bracket (H = 14.104, p = .007). These two significant differences in the group indicate inequity in access to technologies and an information-rich environment at home, which the school system should address. To address the gaps in the perceived college readiness of future business majors, the researcher proposes a two-year intervention program titled Business-Ready: Skill-Building for Future Business Majors, which uses applied learning, mentorship, and business simulation.